Genetic Background of β-Lactamase Genes in Extraintestinal Pathogenic Escherichia coli ST131 in Indonesia Based on Whole-Genome Sequencing (WGS) Sequences - Noor Andryan Ilsan; Sipriyadi Sipriyadi; Melda Yunita; Siti Nurfajriah; Maulin Inggraini (HAYATI Journal of Biosciences, 2022)
Extraintestinal pathogenic Escherichia coli (ExPEC) is a group of pathogens that can colonize the outside of the intestine, such as the kidney, urinary tract, or bloodstream. This study analyzed more about the genetic background of β-lactamase genes among Indonesian ExPEC ST131. Whole-genome sequencing (WGS) sequences from the National Center for Biotechnology Information (NCBI) of Indonesian ExPEC ST131 were taken, then analyzed. Circular genomic mapping and genomic comparison of surrounding genes of β-lactamase in these isolates were generated. blaOXA-1 and blaDHA-1 were analyzed deeply due to their presence in a relatively long contig, making them available for analysis. Indonesian ExPEC ST131 isolates had blaOXA-1 with an identical genetic background of E. coli originating from China and Austria with aac (6’)-1b-cr5 in the downstream and cab83 in the upstream. The blaOXA-1 was also detected in other species, including Klebsiella pneumoniae INF142 originating from Australia and Salmonella enterica S146 from China. While, blaDHA-1 in EC_0406 had an identical genetic background to E. coli 142 and other species such as Shigella sonei FC1428 from India and S. flexneri M2901 from Australia, with Globulin-encoded gene in the upstream and lysR in the downstream. Our findings demonstrate the global spread of β-lactamase genes detected in Indonesian ExPEC ST131. These genes were identical to those isolated from some countries around the world.